(untitled) (Philologia, 2021)
This paper gives an outline of Hiberno-English, starting with its historical background and the most prominent features which distinguish it from other varieties of English. I briefly described its pronunciation, morphology, syntax and vocabulary, i.e. features common to all regional subvarieties, and every feature is followed by at least one contextualized example. Even though Hiberno-English is gradually changing towards British and American standards and slang, it manages to preserve its uniqueness.